Allotment Stories : Indigenous Land Relations under Settler Siege - O'Brien, Jean M.; Justice, Daniel Heath (Book collections on Project MUSE., 2021)
"Land privatization has been a longstanding and ongoing settler colonial process separating Indigenous peoples from their traditional homelands, with devastating consequences. Allotment Stories delves into this conflict, creating a complex conversation out of narratives of Indigenous communities resisting allotment and other dispossessive land schemes. From the use of homesteading by nineteenth-century Anishinaabe women to maintain their independence to the role that roads have played in expropriating Guam's Indigenous heritage to the links between land loss and genocide in California, Allotment Stories collects more than two dozen chronicles of white imperialism and Indigenous resistance, ranging from the historical to the contemporary. At once informing readers while provoking them toward further research into Indigenous resilience, this collection pieces back together some of what the forces of allotment have tried to tear apart"--